Rekayasa Nori Berbahan Baku Pakcoy (Brassica Rapa L.) - Safitri, Jeny; Amien, Elhamida Rezkia; Suharyatun, Siti; Warji, Warji (abe.fp.unila.ac.id, 2024)
Nori is a popular seaweed-based food made from red algae Porphyra. The demand for nori in Indonesia is increasing, but Indonesia does not have Porphyra as raw material and lacks knowledge to find alternatives. Pakcoy (Brassica rapa L.) is a nutritious vegetable that is rarely developed and has the potential to become an alternative raw material for nori. This research aims to develop nori made from pakcoy with various binders to approach commercial nori products. This study is expected to produce an alternative nori that is easily sourced and cultivated in Indonesia. The research used a Completely Randomized Design (CRD) method with 10 treatment levels, which are combinations of 3 types of binders (CMC, tapioca, and cornstarch) at 3 concentration levels (3%, 5%, and 7%). Pakcoy nori was made through the processes of washing, steaming, ginding, molding, and drying. The results of the study show that the addition of 3% CMC produces pakcoy nori with the most preferred color, aroma, flavor, and crispiness by the panelists. The use of CMC, tapioca, and cornstarch as binders can produce pakcoy nori with characteristics similar to commercial nori. This research indicates that pakcoy nori has the potential to be developed as an alternative raw material for nori using 3% CMC as a binder. Keywords: Binder, Brassica rapa L., CMC, Nori, Pakcoy, Porphyra